1996
DOI: 10.1080/02652039609374396
|View full text |Cite
|
Sign up to set email alerts
|

The natural occurrence of fumonisins in Brazilian corn kernels

Abstract: Since animal intoxication related to corn-based feed is frequently observed in the State of Paraná, Brazil, natural contamination by fumonisins in 48 corn samples (39 from the State of Paraná, and 9 from the Brazilian tropical states, Mato Grosso do Sul and Goias) harvested in 1990-1991 was investigated, along with fungal flora. The total mould count ranged from 6.3 x 10(2) to 5.5 x 10(7) cfu/g, and Fusarium moniliforme and Aspergillus species belonging to section Flavi were detected in 41 and 33 samples, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0
14

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 23 publications
7
32
0
14
Order By: Relevance
“…A alta incidência de fumonisinas em milho brasileiro é preocupante, uma vez que um dos primeiros estudos revelou 100 e 97,4% de contaminação por fumonisina B 1 (FB 1 ) e B 2 (FB 2 ), respectivamente (HIROOKA et al, 1996).…”
Section: Introductionunclassified
“…A alta incidência de fumonisinas em milho brasileiro é preocupante, uma vez que um dos primeiros estudos revelou 100 e 97,4% de contaminação por fumonisina B 1 (FB 1 ) e B 2 (FB 2 ), respectivamente (HIROOKA et al, 1996).…”
Section: Introductionunclassified
“…section Flavi were detected in 41 and 33 samples, respectively (48). In a recent survey involving 150 samples of freshly harvested corn from the Central-Southern, Central-Western and Northern regions of the state of Parana, the samples were frequently contaminated with Fusarium spp.…”
Section: Mycological Surveys and Mycotoxin-producing Potentialmentioning
confidence: 99%
“…Francheschi et al (1990) linked the rise in the development of EC in north-eastern Italy to increased corn consumption, in which polenta is the main basic food (Doko and Visconti, 1994) with a possible relation to a human carcinogenic In Brazil, it has been related to outbreaks of toxicosis in animals (Meirelles et al, 1994;Sydenham et al, 1992). There are records of the occurrence of fumonisins in corn and corn-based products, particularly in the Southern and Southwestern regions of the country, with levels that vary from 0.02 to 49.31µg/g for FB 1 and from 0.05 to 29.16 µg/g for FB 2 (Camargos et al, 2000;Hirooka et al, 1996;Ono et al, 2000Ono et al, , 2001Ono et al, , 2002Orsi et al, 2000). In Santa Catarina, FBs studies reported up to 97.3 % of the corn sold is contaminated.…”
Section: Introductionmentioning
confidence: 99%